SF1 and spleen development: new heterozygous mutation, literature review and consequences for NR5A1‐mutated patient's management. Issue 1 (22nd February 2017) - Colson, C.; Aubry, E.; Cartigny, M.; Rémy, A.‐A.; Franquet, H.; Leroy, X.; Kéchid, G.; Lefèvre, C.; Besson, R.; Cools, M.; Spinoit, A.F.; Sultan, C.; et al.
Abstract : Steroidogenic factor 1 (encoded by SF1/NR5A1 ) is a transcription factor with multiple target genes involved in the development and function of multiple steroidogenic and non‐steroidogenic tissues. NR5A1 mutations lead to several phenotypes, including sex reversal, spermatogenesis failure, premature ovarian failure and adrenocortical insufficiency. The implication of NR5A1 mutations in spleen development anomalies was recently highlighted. We provide new evidence of this involvement, describing a novel heterozygous non‐sense NR5A1 mutation in a 46, XY‐DSD with polysplenia female proband and her father, who had hypospadias and asplenia. Abstract :